Behavioral Financial Aspects Analysis on MSMEs Business Development of Culinary Sector in Semarang City - Tyoso, Jaluanto Sunu Punjul; Soegiastuti, Janti (Universitas Dian Nuswantoro Semarang, 2023)
This study was proposed to study and analyze behavioral financial technologies for the development of MSMEs in the culinary field in the city of Semarang. There has been a lot of research related to fintech (fintech) or fintech topics or issues, but not much research has been found on behavioral fintech, especially related to MSME business development. The sample of the study is 125 culinary MSMEs in the city of Semarang. The data collected through the questionnaires was then analyzed using smartpls. This study found that financial satisfaction, owner characteristics, social impact, and risk reduction had a positive (significant) impact on behavioral finance, while financial literacy had a significant negative impact on behavioral finance. Behavioral financial factors have a significant positive impact on MSME business development. This means that Behavioral Finance as a mediation variable between Financial Satisfaction, Owner Characteristics, Financial Literacy, Risk Mitigation, Social Influence variables affecting on business development. Many of them (MSMEs) claimed that they have no experience of using digital technologies themselves, in this case, online transaction applications, and they still did not understand financial literacy. Future research on other variables that do have a positive and significant impact on MSME business development. The sample size also needs to be increased in size and diversity of the MSME sector by at least 60-70% in order for the study to better describe the situation and the state of the MSME.Keywords:behavioral finance, financial satisfaction, financial literacy, risk reduction, social impact business development